Therapeutic Approaches to Counselling Trans and Gender Diverse Clients During the 2017 Australian Marriage Law Postal Survey: A Qualitative Study of the Effects of Stigma - Gaby Mason (Psychotherapy and Counselling Journal of Australia)
The Australian Marriage Law Postal Survey (AMLPS), conducted between September and November 2017, has been identified as a time when trans and gender diverse (TGD) people experienced high levels of societal stigmatisation. This study enquired into the impacts of stigma on TGD people during the period of the 2017 AMLPS. Six experienced therapists reported the experiences of their TGD clients during this period, which included: an increased lack of safety, family ruptures, experiences of distress, and re-triggering of past traumas. This paper describes the approaches adopted by these therapists and documents the resources they drew upon to address the effects of stigma in their clients. Enquiry into approaches utilised by therapists revealed three themes: acknowledging the systems at play, promoting self-care, and working from a trauma-informed approach. The paper also outlines the impacts of structural and interpersonal stigma on TGD people and approaches to counselling reported in the literature when working with the effects of stigma.